Plasma circulating tumor DNA assessment reveals KMT2D as a potential poor prognostic factor in extranodal NK/T-cell lymphoma - Qiong Li; Wei Zhang; Jiali Li; Jingkang Xiong; Jia Liu; Ting Chen; Qin Wen; Yunjing Zeng; Li Gao; Lei Gao; Cheng Zhang; Peiyan Kong; et al. (BMC, 2020)
Abstract Background The early detection of tumors upon initial diagnosis or during routine surveillance is important for improving survival outcomes. Here, we investigated the feasibility and clinical significance of circulating tumor DNA (ctDNA) detection for Extranodal NK/T-cell lymphoma, nasal type (ENTKL). Methods The plasma ctDNA assessment was based on blood specimens collected from 65 newly diagnosed patients with ENKTL in the hematology medical center of Xinqiao Hospital. Longitudinal samples collected under chemotherapy were also included. The gene mutation spectrum of ENKTL was analyzed via next generation sequencing. Results We found that the most frequently mutated genes were KMT2D (23.1%), APC (12.3%), ATM (10.8%), ASXL3 (9.2%), JAK3 (9.2%), SETD2 (9.2%), TP53 (9.2%) and NOTCH1 (7.7%). The mutation allele frequencies of ATM and JAK3 were significantly correlated with the disease stage, and mutated KMT2D, ASXL3 and JAK3 were positively correlated with the metabolic tumor burden of the patients. Compared with the tumor tissue, ctDNA profiling showed good concordance (93.75%). Serial ctDNA analysis showed that treatment with chemotherapy could decrease the number and mutation allele frequencies of the genes. Compared with PET/CT, ctDNA has more advantages in tracking residual disease in patients. In addition, patients with mutated KMT2D had higher expression compared with those with wild type, and mutated KMT2D predicted poor prognosis. Conclusion Our results unveil the mutation spectrum of ENKTL patients' plasma, which can be used to monitor the disease status of the patients exactly, and KMT2D is the most frequently mutated gene with prognosis prediction value. The application of ctDNA sequencing can provide precision treatment strategies for patients. Trial registration This study is registered with chictr.org ( ChiCTR1800014813 , registered 7 February, 2018-Retrospectively registered).